Anthropometric profile of football goalkeepers from the national teams participating in the World Cups among 2002/2014: a comparative study - Silva, Daniel Ricardi Crizel da (2021)
A specific football position, the goalkeeper, has the main function of defending the goal, which measures 244 (cm) in height by 732 (cm) in width. For that, larger parameters seem to emerge in relation to the height of this athlete. This study aimed to describe the height profile of the goalkeepers from de national teams that played the World Cups in 2002, 2006, 2010 and 2014. In addition, the study aimed to analyse the variations in height over this period. This is a descriptive study and the sample consisted of 384 goalkeepers, 96 in each tournament. To verify the differences between the means of height (stratified by continents and world event), the Anova one-way statistical test was used. When the F test was significant, the differences between the groups were analyzed by Bonferroni post-hoc test. There was no significant variation among the heights over the world cups. In 2002, there was no significant difference between continents, a result that was not repeated in the other editions of the tournament. The observed variability may be the result of ethnic differences among different peoples, or even of social, economic and cultural conditions, with the developed countries offering better live conditions, thus influencing the anthropometric profile of the population. Finally, the natural selection of the sport, together with the development of the sports sciences also point to an increase in stature. It is important to deepen this theme, in a longer time frame, showing better the variability of the stature from the goalkeepers and correlating it with their efficiency level.